Helminthfauna of the Bukhar deer (Cervus elaphus bactrianus Lydekker, 1990) are advertised rare species in Kazakhstan again (Experimental biology, 2015)
The species composition are showed and are revealed some issues of ecology and biology of helminths of rarespecies the Bukhara deer (Cervus elaphus bactrianus Lydekker, 1990) in the Karachingilsk hunting ground and in thenursery of the flood plain Syr Darya River of South Kazakhstan.
Keywords: а common rats; a respondent; a number; an area of distribution and a questionnaire.